Greening Information Technology: E-waste Management Approach - Omar, Adnan; Ezeluomba, Chukwuka; Belmasrour, Rachid (International Journal For Research In Advanced Computer Science And Engineering, 2015)
In recent years, as rapid growth and innovation occur in the technological sector of the economy, most business organizations have realized the need for greening their information technology for reasons both of social responsibility and reduction of the costs of operation. Also, government agencies have contributed to Greening Information Technology (GIT) by initiating programs and regulations that enforce it. The idea behind the GIT is to focus on ways of reducing the technological footprint on the environment. This is done by promoting new approaches in reducing pollution on the environment through effective disposal and recycling of defunct information technology (IT) products and factory waste. This paper presents electronic waste (e-waste) management from the manufacturer’s and consumer’s perspectives and by using statistical technique to determine the economic significance of revenue generated from recycling e-waste.